Seed cryopreservation, in vitro propagation and ex vitro growth of Cattleya walkeriana Gardner, a vulnerable ornamental orchid - Galdiano, Renato Fernandes [UNESP]; Vendrame, Wagner Aparecido; Moretto, Cristiane [UNESP]; de Faria, Ricardo Tadeu; Lemos, Eliana Gertrudes de Macedo [UNESP] (Southern Cross Publishing, 2017)
The aim of this investigation was to evaluate cryopreservation by vitrification of seeds from the orchid species Cattleya walkeriana and to achieve ex vitro acclimatization of in vitro derived cryopreserved seedlings. Seeds were removed from eight-month-old and ten-month-old capsules, and immersed in LN under different PVS2 exposure times. In in vitro experiment, ten different treatments and five replications with approximately 600 seeds each one were distributed in a completely random design and germination was calculated by the number of germinated seeds developing into protocorms and subsequently into seedlings. Seeds that were immersed directly into LN (0 min PVS2) and germinated in 1/2 MS culture medium after plunged directly into LN, returned germination rates of 3.0 (eight-month-old) and 36.8% (ten-month-old). Ten-month-old seeds in vitrification for 1h in PVS2 returned 53% germination in 1/2 MS culture medium. However, when the same mature seeds were exposed for 1h to PVS2 with the addition of 1% phloroglucinol, germination was 4.36% higher compared to the treatment without this additive. Seedlings from cryopreserved seeds showed normal development after 210 days of in vitro culture. Seedlings from ten-month-old seeds cryopreserved for 1h in PVS2 were acclimatized in greenhouse conditions in either sphagnum moss or sphagnum moss with pine bark (1:1, v/v) revealed the best ex vitro growth. Seed cryopreservation of this orchid species has shown to be efficient, demonstrating the effect of seed maturation time and ex vitro seedling acclimatization was established, with successful development of seedlings.
Keywords: Acclimatization; Germplasm conservation; Orchidaceae; Phloroglucinol; Vitrification